THE ANALISIS PERILAKU GEN-Z DAN PENGGUNAAN MEDIA SOSIAL TERHADAP PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KOTA BOGOR: ANALISIS PERILAKU GEN-Z DAN PENGGUNAAN MEDIA SOSIAL TERHADAP PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KOTA BOGOR - Allinny Kurnia Sabandiyah; Dhanik Puspita Sari (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
Generation Z (Gen-Z) is a group of travelers who are closely connected to social media, which helps them plan their trips and share their travel experiences. This study was conducted to analyze Gen-Z behavior and the use of social media in relation to the development of sustainable tourism in Bogor City. The method used is descriptive quantitative, utilizing questionnaires distributed to 100 Gen-Z individuals who visited Bogor City. Data analysis was performed using SPSS with a multiple linear regression approach. The results show a positive and significant relationship between Gen-Z behavior, social media usage, and the development of sustainable tourism in Bogor City (r = 0.746 and p = 0.00). Generation Z not only acts as tourists but also as promotional agents through social media, capable of disseminating information and shaping public opinion on the importance of sustainability in tourism. This study suggests the need for digital promotion strategies that are better aligned with the profile of Gen-Z, so that they are more widely accepted, impactful, and targeted.